Pentamidine Is a Specific, Non-Peptide, GPIIb/llla Antagonist - Cox, Dermot; Aoki, Toshiaki; Seki, Jiro; Motoyama, Yukio; Yoshida, Keizo (Thrombosis and Haemostasis, 1996)
Pentamidine was previously shown to act on glycoprotein (GP) Ilb/IIIa (Cox et al., Thromb Haemost 1992; 68: 731). In this paper we study the effect of pentamidine on other RGD-dependent receptors. In a cell adhesion assay, pentamidine was 500 times more potent than RGDS at inhibiting platelet adhesion to fibrinogen. While RGDS inhibited platelet adhesion to fibronectin, endothelial cell adhesion to vitronectin or fibronectin, 293 cell adhesion to vitronectin, IMR 32 cell adhesion to fibronectin and C32 cell adhesion to vitronectin; pentamidine failed to inhibit these interactions at doses as high as 1 mM. Resting platelets fixed in the presence of 1 mM RGDS had increased binding of fibrinogen, i.e., RGDS activated GPIMIIa, while pentamidine at 100 ΜM had no effect. Similarly, RGDS induced the binding of an anti-LIBS monoclonal antibody, while pentamidine had no effect. Pentamidine partially, but significantly, inhibited lysosome and a-granule release induced by the thrombin agonist peptide, while RGDS had no effect. Neither pentamidine nor RGDS affected ADP-induced Ca2+ influx. Pentamidine had no effect on ADP-induced intracellular pH changes while RGDS prevented the pH from returning to normal. Thus, pentamidine is a non-peptide GPIIb/IIIa antagonist that is non-activating and is specific for GPIIb/IIIa.